Shaping Students’ Politeness through Bilingual Mentoring in Rural Elementary Schools: A PRISMA-based Systematic Literature Review - Wibowo, Agung Tri; Yamtinah, Sri; Sukarno, Sukarno (Universitas Sebelas Maret, 2026)
Language politeness among elementary school students remains a concern, as many still demonstrate inappropriate ways of speaking. This study aims to examine bilingual politeness mentoring in rural elementary schools using a systematic literature review (SLR) design. Data were collected through the PRISMA method from publications indexed in Google Scholar, Scopus, and ScienceDirect between 2021 and 2025. A total of 48 articles were initially identified, focusing on two main aspects: (1) teacher mentoring in bilingual politeness and (2) school-based programs supporting politeness development. The findings reveal that teacher mentoring plays a significant role in shaping students’ language politeness through modeling, habituation, and interaction. In addition, school programs support this process by facilitating communication and strengthening teacher–student relationships. In boarding school contexts, these programs enable teachers to take on extended roles as parental figures, fostering closer relationships and promoting respectful and polite communication among students.